Small-signal stability, control and dynamic performance of power systems - Gibbard, M.J (University of Adelaide Press, 2015)
A thorough and exhaustive presentation of theoretical analysis and practical techniques for the small-signal analysis and control of large modern electric power systems as well as an assessment of their stability and damping performance. Such systems may contain many hundreds of synchronous generators and high voltage power electronics equipment known as FACTS Devices. The book describes new techniques not only for the tuning and analysis of stabilizers for systems with many generators and FACTS Devices but also for their coordination. Of practical interest, these techniques are illustrated with relevant examples based on a multi-machine power system containing FACTS Devices for operating conditions ranging from light to peak load. By introducing new analytical concepts, using examples, and by employing production-grade software, practical insights are provided into the significance and application of various analytical techniques.